Thrive: Seven Steps to Successful Self-Leadership - George Wilkinson (UK Red Door, 2020)
It has never been more important to be able to manage your time, your resources and your self effectively. The home and working landscape has changed immeasurably and finding ways to adapt, push on and thrive is essential. In this timely and necessary book, George Wilkinson draws on his own and others experiences, to provide clear and practical steps to reframe perspective and turn new experiences into positive lessons in self-leadership. The book focuses on seven key elements: Achieving Success - The science behind personal success Perseverance - How we can use perseverance to reach our goals Emotional Mastery - How clever emotional management can unlock a whole new life Embracing Failure - Why we must accept and embrace failure to succeed Decision-Making - A simple process to make those key decisions Leading Others - Why true leadership must start from within Serving Others - How service to others brings about success for us Packed with case studies and backed by research that illustrates the seven key elements of the book, Thrive: 7 Steps to Successful Self-Leadership provides the reader with the tools they need to regain and improve their self-management skills, leading to positive outcomes at work and home.
Keywords: Business; Leadership; Self Help; Nonfiction